The Cell-Penetrating Peptide Tat Facilitates Effective Internalization of PSD-95 Inhibitors Into Blood–Brain Barrier Endothelial Cells but less Efficient Permeation Across the Blood–Brain Barrier In Vitro and In Vivo - Al Humaidan, Emma Lisa; Pedersen, Sidse Lund; Burkhart, Annette; Rasmussen, Charlotte Laurfelt Munch; Moos, Torben; Fuchs, Peter; Fernandes, Eduardo Filipe Alves; Ozgür, Burak; Strømgaard, Kristian; Bach, Anders; Brodin, Birger; Kristensen, Mie (Frontiers in Drug Delivery, 2022)
Inhibition of the interaction between the scaffolding protein PSD-95 and the NMDA receptor has been shown to obstruct ischemic stroke-triggered excitotoxic reactions, leading to neuronal death. The peptides NR2B9c and N-dimer are inhibitors of this interaction. Delivery of the peptides to the brain is challenging due to the general low blood–brain barrier (BBB) permeability. NR2B9c and N-dimer have therefore been conjugated to the cell-penetrating peptide (CPP) Tat, to facilitate blood–brain barrier permeation. However, the BBB permeation of Tat-NR2B9c and Tat-N-dimer has not been fully elucidated. We recently demonstrated that the BBB permeation in vitro and in vivo was lowered upon conjugation of NR2B9c or N-dimer to Tat. In the present study, we aimed to further understand the impact of cargo conjugation to Tat with respect to interaction with and permeation across the BBB in vitro and in vivo. The peptides were labeled with the fluorophore TAMRA (T) and demonstrated efficient Tat-mediated uptake into BBB endothelial cells but differed in their degree of plasma membrane interaction and embedding (T-Tat-NR2B9c = T-Tat > T-Tat-N-dimer) as well as in their chemical stability (T-Tat-N-dimer = T-Tat > T-Tat-NR2B9c). The Tat conjugates all displayed a similar degree of self-association and/or plasma protein adsorption. T-Tat-NR2B9c and T-Tat affected the BBB integrity but not the permeation of the paracellular marker C14-mannitol. T-Tat-NR2B9c and T-Tat-N-dimer displayed less efficient permeation across an in vitro model representing the healthy BBB, when compared to T-Tat, and low BBB permeation in healthy rats.